Developed and validated inoculation and disease assessment methods for Goss's bacterial wilt and leaf blight disease of corn. (October 2018) - Soliman, Atta; Gulden, Robert H.; Tambong, James T.; Bajracharya, Pratisara; Adam, Lorne R.; Xu, Renlin; Cott, Morgan; Daayf, Fouad
Abstract: One of the drawbacks of conducting research on Goss's bacterial wilt and leaf blight disease, caused by the bacterium Clavibacter nebraskensis (Cn) on corn ( Zea mays L.), is the lack of standardized and validated inoculation and disease assessment methods. Here we report foliar and root inoculation techniques with a standardized scale for reliable assessment of symptoms to allow for disease assessment of the Goss's wilt disease on corn. The leaf inoculation method allowed for the application of equal amounts of inoculum, which ensured consistency in measurements and prevented inoculum run off from the inoculation site. The reliability of a leaf inoculation method based on either lesion length or disease severity, and root inoculation based on disease severity was validated statistically using two Cn isolates, Cmn14-5-1 and DOAB232, which possess high and low levels of aggressiveness, respectively. The leaf disease-severity and the lesion length methods for disease assessment clearly provided the most precise estimation of the level of aggressiveness of Cn isolates among the tested years (2015, 2016, and 2017 growing seasons). In addition, the disease severity based on the root inoculation method was validated, but the high variation among experimental runs within each year suggested that it might be the least reliable method for assessment of the disease severity. Our results indicated no significant trend in overall isolate aggressiveness over the years using the leaf inoculation method based on either lesion length or leaf disease-severity. Highlights: Standardized inoculation and assessment methods are missing for Goss's wilt of corn. Leaf disease-severity and lesion length provided precise estimation of aggressiveness. No variation trend in Clavibacter nebraskensis aggressiveness over the years in Manitoba.